2016
DOI: 10.6004/jnccn.2016.0049
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Initial Care for Medicare Patients With Advanced Ovarian Cancer

Abstract: The mean total payment per patient in the initial treatment period was $65,908 (range of means, $30,745-$96,360). Increasing medical comorbidity, use of PET/CT, surgical complications, and readmissions were associated with increased costs. Treatment with NCCN Guideline-consistent surgery and chemotherapy had a mean annual cost of $85,987 compared with $89,149 for non-NCCN Guideline-consistent treatment with surgery and chemotherapy. The cost of surgery and chemotherapy that was not consistent with NCCN Guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…The mean payments for Medicare beneficiaries with ovarian cancer within the first year of diagnosis was $65,908, Treatment with guideline concordant care was associated with lower costs in this cohort. 8 These findings are in line with our data in which payments of $93,000 within the first year of diagnosis for commercially insured women with ovarian cancer.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mean payments for Medicare beneficiaries with ovarian cancer within the first year of diagnosis was $65,908, Treatment with guideline concordant care was associated with lower costs in this cohort. 8 These findings are in line with our data in which payments of $93,000 within the first year of diagnosis for commercially insured women with ovarian cancer.…”
Section: Discussionsupporting
confidence: 88%
“…69 A recent study of Medicare beneficiaries estimated that the mean cost of care during the first year after diagnosis was approximately $66,000. 8 Estimates of how these costs are shared by patients are limited. The objective of the study was to examine the cost of care during the first year after diagnosis, to estimate the sources of cost, and to investigate the out-of-pocket costs that women with ovarian cancer experience.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when considering costs from a societal perspective, one study reported that an estimated $2.5 billion was spent in 2010 for 10 common chemotherapies that were used in discordance with NCCN recommendations. 17 Similarly, in a SEER-Medicare analysis of almost 10,000 patients with ovarian cancer, Urban et al 18 found $7,500 higher Medicare spending for patients receiving guideline-discordant chemotherapy and surgery versus for concordant treatment in the first year after diagnosis. Although these and other studies have shown associations between guideline discordance and increased payer costs, patients themselves are largely unaware of and indifferent to payer or societal care costs outside of their immediate responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…Receipt of non-NCCN guideline-consistent care has previously been shown to be an independent predictor of diminished overall survival in women with ovarian cancer [21]. Additionally, non-NCCN guideline-consistent care has been associated with greater overall costs for the treatment of women with ovarian cancer [30]. Guideline-consistent care provides the definition of value in healthcare with both improved outcomes and lower costs.…”
Section: Discussionmentioning
confidence: 99%